2023
DOI: 10.55322/mdbakis.1106587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mixed and Accrued Models in Earnings Management and an Application

Abstract: Dünya genelinde yaşanan muhasebe skandalları sebebiyle yankıları çokça hissedilmeye başlayan ekonomik kayıplar, bakışların kazanç yönetimi üzerine çevrilmesine sebep olmuştur. Yaşanılan skandallarda firma yöneticilerinin manipülatör davranışlar sergileyerek finansal tablolarını olduğundan farklı bir şekilde yayımlaması, yatırımcıların, ekonomistlerin ve kreditörlerin akıllarında soru işaretleri oluşmasına sebep olmuştur. Ortaya çıkan bu olumsuz durum kazanç yönetimi tespiti ve uygulanabilirliği konusunda geniş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Gür and Tarhan Mengi (2022) used DT, SVM, Logistic Regression, and ANNs methods to detect fraud, and it was determined that the most accurate prediction model was created by the DT method. Kılıç and Önal (2022), Kara and Özcan (2020), Terzi and Kıymetli Şen (2012) used ANNs data mining method. Uğurlu and Sevim (2015) concluded that the ANNs model predicts more successfully than other models in estimating fraudulent financial statements.…”
Section: Data Mining In Fraud Detectionmentioning
confidence: 99%
“…Gür and Tarhan Mengi (2022) used DT, SVM, Logistic Regression, and ANNs methods to detect fraud, and it was determined that the most accurate prediction model was created by the DT method. Kılıç and Önal (2022), Kara and Özcan (2020), Terzi and Kıymetli Şen (2012) used ANNs data mining method. Uğurlu and Sevim (2015) concluded that the ANNs model predicts more successfully than other models in estimating fraudulent financial statements.…”
Section: Data Mining In Fraud Detectionmentioning
confidence: 99%
“…Literatür incelendiğinde birçok farklı model kullanılarak muhasebe manipülasyonunun yapılıp yapılmadığını belirlemeyi hedefleyen ulusal ve uluslararası araştırmalar yer almaktadır (Agustia, v.dğr., 2020;Almamy, v.dğr., 2016;Kara & Tuna, 2018;Kirkos, v.dğr., 2007;Özevin, 2020). Bu modeller genellikle iki veya üç başlık altında incelenmektedir: Tahakkuk Esaslı Modeller, Karma Modeller, Alternatif Modeller (Kıllı & Evci, 2017;Güner & Kurnaz, 2020, s. 202).…”
Section: Introductionunclassified